PENGARUH KEMAMPUAN LITERASI MATEMATIKA DALAM PENYELESAIAN SOAL CERITA SISWA KELAS V DI SDN 064986 MEDAN - Daliani, Muhammad; Widiyarti, Gemala; Sihombing, Enjelica; Simanjuntak, Nurkhairati (Universitas Quality, 2025)
Literacy culture is very important for everyone. It can broaden a person's insight. Literacy is a person's ability to read, write, understand, interpret, and use information well. Literacy also occurs in mathematical skills, mathematical literacy is defined as an essential ability that functions as a foundation for students in understanding, analyzing, and solving problems in the form of story problems. In this context, mathematical literacy is not just the skill of calculating or applying formulas, but also the ability to connect mathematical concepts with real-life situations. The influence of mathematical literacy on solving story problems is clearly seen in the aspects of understanding context, interpreting information, and choosing a solution strategy. Story problems related to everyday life are presented so that students can examine problems by reasoning in everyday life, so that students are able to communicate their opinions correctly and precisely. The research method used in this study is a quantitative method. The population in this study were grade V students of SDN 064986 Medan with a total of 25 students. The purpose of this study was to determine the level of students' mathematical literacy in solving story problems and to identify obstacles faced in the process. The hypothesis of this study can improve mathematical literacy skills in solving story problems.